High-Density Nanoporous carbon materials as storage material for Methane: A value-added solution; Chemical Engineering Journal; Vol. 433 - Memetova A. Anastasia; Tyagi I. Inderjeet; Rao K. R. Karri Rama; Memetov N. Nariman; Zelenin A. Andrey; Stolyarov R. Roman; Bogoslovsky (Bogoslovskiy) V. Vladimir (2022, 2022)
Title screen